COVID-19: Molecular and Cellular Response - Alipoor, Shamila D.; Mortaz, Esmaeil; Jamaati, Hamidreza; Tabarsi, Payam; Bayram, Hasan; Varahram, Mohammad; Adcock, Ian M. (Frontiers in Cellular and Infection Microbiology, 2021)
In late December 2019, a vtiral pneumonia with an unknown agent was reported in Wuhan, China. A novel coronavirus was identified as the causative agent. Because of the human-to-human transmission and rapid spread; coronavirus disease 2019 (COVID-19) has rapidly increased to an epidemic scale and poses a severe threat to human health; it has been declared a public health emergency of international concern (PHEIC) by the World Health Organization (WHO). This review aims to summarize the recent research progress of COVID-19 molecular features and immunopathogenesis to provide a reference for further research in prevention and treatment of SARS coronavirus2 (SARS-CoV-2) infection based on the knowledge from researches on SARS-CoV and Middle East respiratory syndrome-related coronavirus (MERS-CoV).